2015
DOI: 10.1007/s12011-015-0537-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trace Elements and Their Relationship with Growth and Development of Young Children

Abstract: This study was conducted to assess the levels of trace elements and their relationship with growth and development of children in Shanghai, China, to offer scientific evidence for supplementing trace elements in children. A stratified, clustered, random sampling method was used in the study. Blood samples were taken from 2141 Shanghai children from 0 to 6.0 years old, and the concentrations of zinc (Zn), calcium (Ca), iron (Fe), copper (Cu), and magnesium (Mg) were measured using inductively coupled plasma mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
2
17
1
1
Order By: Relevance
“…Intestinal copper absorption occurs very efficiently, and copper excess is removed by the liver and excretion with bile into feces, in the order of 4.5 mg/day [6] . However, most of the copper secreted with the bile is reabsorbed by enterocytes [34,35] , and the copper concentration in Chinese children's blood is around 1 mcg/ml [36] . In addition, the intestinal copper absorption is inversely proportional to the copper content in the diet, being reduced to about one-tenth in high-copper diets [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal copper absorption occurs very efficiently, and copper excess is removed by the liver and excretion with bile into feces, in the order of 4.5 mg/day [6] . However, most of the copper secreted with the bile is reabsorbed by enterocytes [34,35] , and the copper concentration in Chinese children's blood is around 1 mcg/ml [36] . In addition, the intestinal copper absorption is inversely proportional to the copper content in the diet, being reduced to about one-tenth in high-copper diets [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Micro nutrients include a number of elements which are required in trace amounts to drive critical biochemical processes in the body. These come mainly from intestinal absorption, following oral ingestion [14]. As a result, their metabolism tends to interact either synergistically or antagonistically and this could be important in a number of disease states [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, their metabolism tends to interact either synergistically or antagonistically and this could be important in a number of disease states [15,16]. This observation is demonstrated in nutritional anemia, in which the intestinal absorption of iron is up regulation along with that of other divalent metals, leading to their altered serum levels [14,17]. It has been observed that micro nutrients such as zinc and copper impair iron absorption and could predispose to the development of anemia [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biologically, Zn has three main functions: catalysis, adjustment, and structure. Zn, an enzyme constituent [11,13], also catalyzes enzymatic reactions and plays an important role in metabolism [14,15], tissue respiration [16,17] and regeneration [18,19], and growth [17,20]. Zn may also affect the effectiveness of hormone receptor and target organ responses; hormone production, storage, and secretion; and sexual development [21,22].…”
Section: Introductionmentioning
confidence: 99%